Prevalence and reasons for seeking treatment for oral health problem at 3 selected medical primary care clinics in Kuantan, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Sulong, Robiatu Adawiah (2014)
Oral health as an integral part of general health. Beside, sharing common risk factors between oral health and general health have been found more since late nineteen century. The evidences of seeking treatments for oral hearth problems (OHLs)with primary care physicians (PCPs) at medical primary care clinics (MPCCS) were noticed in the morbidity reports treatment from PCPs for OHPs at MPCCs have been still unclear. Objective:to explore prevalence and reasons for seeking treatment for oral health problems in 3 medical primary care clinics in Kuantan. Methods: A pilot study was conduct by applying mixed method (Quantitative and Qualitative) approach among 3 MPCCs of Kuantan - University Clinic (IIUM), Public Clinic (Balok) and Private Clinic named Ar Razi- from April,2012 tp March 2013. Total OHPS cases were retrieved from electronic patient record system of the respective clinic and volunteer sampling method was used to collect quantitative data by a guide question set among 10 cases collect qualitative data regarding reasons for seeking treatment for OHPs at 3 transcriptions. Results : Total 623 cases were retrieved from 3 MPCCs within one year. Prevalence of OHPs in the University clinic,Public clinic (Balok) and Private clinics (Ar Razi) were 9.3,10.9 and 5.4 per 1000 patients per year with average 7.4/1000 patients per years. All night call cases were from the private clinic Ar-Razi which was 15.5% (154/268) of total OHPs of this private clinic. The most reason for encounter (RFE)was mouth ulcer (50.4%) followed by gingivitis (17.7%), toothache (12.6%), painful gum (8.9), hand-foot-mouth-disease (7.8%), gum abscess (1.8%),more than one RFE (0.5%) and teething (0.3%). RFEs among 3 different medical primary care clinics were significant different (p 0.05). Most of reasons for seeking treatment for OHPs can be treated by PCPs. More understandable reasons of the patients such as co-morbility with medical symptoms, familiarity with PCPs and un-familiarity with dentists and dental phobia were confirmed in qualitative study. Comclusion: This study highlighted that OHPs is one of RFEs in MPCCs and role of PCPs in primary and emergency oral health care. More understandable answers for seeking treatment from PCPs for OHPs at MPCCs were provided. Coordinated care between PCPs and dentists should be promoted for OHPs with medical disease. A further planning to provide better care for patients with OHPs in MPCCs should be considered.